The Effect of Communication, Work Stress and Compensation on Employee Performance at CV. Mandiri Putra Jaya - Indra Irawan; Ari Sulistyowati; Christoporus Indra Wahyu; Tyna Yunita (Draf Solusi Indonesia, 2023)
To achieve the goals of a company, employee performance is needed which is a driving factor for the creation of every organization in the company. However, to support the achievement of company goals, there are several factors that are strong and perfect employee performance, such as Communication, Work Stress, and Compensation. The purpose of this study is to find out whether there is an Effect of Communication, Work Stress and Compensation on Employee Performance. The analysis method used is quantitative analysis. Using non-probability sampling research techniques with data analysis methods Validity Test, Reliability Test, Classical Assumption Test, Regression Analysis and Hypothesis Test using partial and simultaneous. Communication t Test Results (X1) of 2,285 with a sig value of 0.005, Work Stress (X2) of 2,715 with a sig value of 0.008, Compensation (X3) of 2,636 with a sig value of 0.001, Test Results F Communication Variables (X1), Work Stress (X2) and Compensation (X3) on Employee Performance (Y) of 14,803 and a sig value of 0.000 Multiple Linear Regression Test Results Employee performance with a constant value of 4,226, Communication Variable (X1) of 0.204 Work Stress Variable (X2) of 0.232 and Compensation Variable (X3) of 0.262..